2009
DOI: 10.1254/jphs.08173fp
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Mediated Enhanced Apoptotic Action of Cyclophosphamide- and Resveratrol-Treated MCF-7 Cells

Abstract: Abstract. Cyclophosphamide (CPA) is a widely used chemotherapeutic drug for neoplasias. It is a DNA and protein alkylating agent having a broad spectrum of activity against a variety of neoplasms including breast cancer. The therapeutic effectiveness of CPA is limited by the highdose hematopoietic, renal, and cardiac toxicity that accompanies the systemic distribution of liver-derived activated drug metabolites. The present study examines the potential of combining resveratrol (RES) with CPA and aims to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Nevertheless, in U937 cells, overexpression of Bcl2 attenuates RES-mediated apoptosis by blocking caspase-3 activation [53]. Moreover, RES induces caspase-dependent and -independent apoptosis in various cancer cells [8587]. In colon cancer cells, RES induces caspase-2 activation that subsequently triggers Bax-Bak-dependent and -independent cell death [79].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in U937 cells, overexpression of Bcl2 attenuates RES-mediated apoptosis by blocking caspase-3 activation [53]. Moreover, RES induces caspase-dependent and -independent apoptosis in various cancer cells [8587]. In colon cancer cells, RES induces caspase-2 activation that subsequently triggers Bax-Bak-dependent and -independent cell death [79].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the modulation of cell fate by polyphenols may be mediated through any of the numerous molecular mechanisms and signalling pathways that regulate (1) the activation of mitochondria and death caspases, (2) the up-regulation of cyclin-dependent kinase inhibitors, tumour suppressor gene products, or death-inducing cytokines and cytokine receptors, and (3) the downregulation of cell survival proteins or inhibition of cell survival kinases and survival transcription factors. [91][92][93][94][95][96][97][98] In this regard, an interesting paper by Kartal et al demonstrates in a cell model of myeloid leukaemia that the pro-apoptotic activity of resveratrol is mediated by increased generation and accumulation of apoptotic ceramides, bioactive sphingolipids that regulate many signalling pathways. 99 Kaempferol induces apoptosis by inactivating Akt, which is one of the most effective anti-apoptotic survival pathways in mammals, and by decreasing the expression of Bcl-2 and increasing the expressions of Bax, eventually inducing the intrinsic pathway in myelogenous leukaemia cell line K562 and promyelocitic human leukaemia U937 cells.…”
Section: Alterations Of Signalling Cascadesmentioning
confidence: 99%
“…The interaction or balance among these pathways finally decides the fate of cells. It has been shown that the activation of SIRT1 in different cells may act in two ways; one is to protect cells from the apoptosis induced by various conditions through regulating the expression and activity of the FOXO family; the other is to induce the activation of the caspase family and promote cell apoptosis (21,22). It has been shown that SIRT1 inhibits angiotensin II-induced vascular smooth muscle cell hypertrophy through modulating nicotinamide adenine dinucleotide phosphate oxidase 1 and GATA binding protein 6 (23).…”
Section: Discussionmentioning
confidence: 99%